Integrating extensive reading in first-year English-Major intensive reading courses: a survey at Tra Vinh university - Nguyen Thi Ngoc Huong (Trường ĐH Mở TP. HCM, 2022)
This study investigated the first-year English major students’ responses to and suggestions on the implementation of Extensive Reading (ER) in their Intensive Reading (IR) courses in two semesters in order to give students and the instructor the experience to reflect how it was done and would be done better in the future as well as getting the language benefits. The twenty-nine participants practiced ER in the fifteenth weeks of semester one and one more participant joined the group in semester two in the same treatment duration of time. Students read graded readers and Andrew Lang’s fairy stories out of class time and wrote reading logs of what they read and kept the reading record to reach the target of 250 and 500 pages of ER in semester one and two respectively. Besides informal discussions, journals and interviews, a survey questionnaire was used to collect the data from students. The findings showed that students had positive responses to ER and gave valuable constructive suggestions to improve ER as they found ER benefits in improving their reading skills, reviewing their grammar and increasing their vocabulary. Several pedagogical implications in implementing ER were withdrawn from this experiment.